2010
DOI: 10.1007/s11250-010-9626-y
|View full text |Cite
|
Sign up to set email alerts
|

Septicemic salmonellosis in a two-humped camel calf (Camelus bactrianus)

Abstract: A 1-week old, two-humped female camel (Camelus bactrianus) calf with continual whining, epiphora, anorexia, muscle twitching, and lateral recumbency was referred to a veterinary hospital. Although she died shortly after preliminary clinical examination, but necropsy was performed and tissue samples were taken for further microbiological and pathological examinations. On bacteriological investigation, Salmonella typhimurium and Streptococcus agalactiae were isolated. Histopathologically, lesions consisted of hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…were contaminated with S. Typhimurium (Nour-Mohammadzadeh et al, 2010). Cross-sectional studies on camels revealed that 43% and 100% of camel milk samples were infected by Salmonella spp.…”
Section: Salmonellosismentioning
confidence: 99%
“…were contaminated with S. Typhimurium (Nour-Mohammadzadeh et al, 2010). Cross-sectional studies on camels revealed that 43% and 100% of camel milk samples were infected by Salmonella spp.…”
Section: Salmonellosismentioning
confidence: 99%
“…Nevertheless, diverse occurrence of this pathogen has been reported in camels in the literature; some authors showed a low presence of Salmonella (Wernery, 1992), while others reported a medium or high prevalence in captive dromedaries (Molla et al, 2004;Moore et al, 2002;Münch et al, 2012;Tejedor-Junco et al, 2010). As in this study, salmonellosis in dromedaries is generally asymptomatic, although clinical Salmonella infections have been reported with symptoms that included epiphora, anorexia, muscle twitching and lateral recumbency (Nour-Mohammadzadeh et al, 2010). In addition, controlling Salmonella infections in camels should be taken into account, as it has been shown that Salmonella could be the cause of co-infections such as clostridia or theileriosis diseases (Abdelwahab et al, 2019).…”
Section: Discussionmentioning
confidence: 80%